Effective use of semi-elemental diet in managing anastomotic leakage after surgery for esophageal stricture: A case report - Afifa, Nadhira Nuraini; Sonia, Steffi; Sunardi, Diana; Lestari, Wiji (Indonesian Nutrition Association, 2024)
Anastomotic leakage occurs in ±10% of patients after surgery for esophageal stricture. Management often requires re-surgery, which increases morbidity and mortality. This case report shows successful conservative management of anastomotic leakage with semi-elemental diet.